Operation of ULCS - real life - Prpić-Oršić Jasna; Parunov Joško; Šikić Igor (International Journal of Naval Architecture and Ocean Engineering, 2014)
In this paper the real life operation of ULCS (Ultra Large Container Ships) is presented from the point of view of shipmasters. The paper provides interpretation of results of questionnaire filled by masters of large container ships during Tools for Ultra Large Container Ships (TULC) EUI FP7 project. This is done in a way that results of questionnaire are further reviewed and commented by experienced master of ULCS. Following phenomena are subject of questionnaire and further discussed in the paper: parametric rolling, slamming, whipping, springing, green water and rogue waves. Special attention is given to the definition of rough sea states as well as to measures that ship masters take to avoid them as well as to the manoeuvring in heavy seas. The role of the wave forecast and weather routing software is also discussed.